In a manner of speaking: assessing frequent spoken figurative idioms to assist ESL/EFL teachers - Grant, L (Elsevier, 2007)
This article outlines criteria to define a figurative idiom, and then compares the frequent figurative idioms identified in two sources of spoken American English (academic and contemporary) to their frequency in spoken British English. This is done by searching the spoken part of the British National Corpus (BNC), to see whether they are frequent on both sides of the Atlantic, or more common in one country or the other. It also compares the figurative idioms identified as frequent in two British idiom dictionaries to see whether their frequency of occurrence in the BNC justifies their ‘frequent’ label. The main aim of the frequency comparisons is to help teachers decide which, if any, are useful to teach to EFL/ESL students so pedagogical implications are also discussed briefly.
Keywords: Figurative idioms; Spoken American English; British National Corpus; Multiword units (MWUs); EFL/ESL teaching